ANALISIS FAKTOR-FAKTOR KEPUTUSAN PEMBELIAN MAKANAN ONLINE MUSLIM MILLENIAL - Arian Agung Prasetiyawan; Sela Mahribi Nurhidayah (Academica: Journal of Multidisciplinary Studies, 2020)
This research aims to find out the factors of online food purchasing decisions in young Muslims as a productive age group of internet users in Indonesia. This sample of research is a student of the Islamic Institute of Surakarta State. Then the study analyzed how halal awareness, curiosity, lifestyle, promotion, favorites, packaging, price and taste affect them in online purchases. The research method used is a mixture of quantitative and qualitative data. The source of this research data is obtained through the dissemination of questionnaires and semi-structured interviews with scoring analysis methods by rating the answers of respondents and drawing statement conclusions from interview answers. The results of this study make halal awareness a priority factor in making online purchases in order of halal awareness priorities; lifestyle; taste; packaging; curiosity; favorites; price; advertising and the majority of IAIN Surakarta students some 642 respondents noticed aspects of product halalness in online food purchases.Keywords:Â Purchasing Decision Factors; Food; Online Purchase; Muslim MillennialÂ